The Professionalism Of Teachers In Public Elementary School State Of West Perak, VI No 494, Dolphin Street No. 29 City Of Surabaya - Wasty Tabita Nubatonis; Surja Permana (Jurnal Didaskalia, 2021)
Professional teachers hold the main key to improving the quality of education in the future. As for the formulation problem in this study, how is the professionalism of teachers in Elementary school State of West Perak VI?. This study aims to determine the professionalism of teachers in Elementary school State of West Perak VI . The approach used in this research is Qualitative with the interview method. The research data dan comes from the headmaster and teachers. The subjects of this study were four informants, namely one headmaster, one Christian religion subject teacher and two class teachers. The reason the researcher took the subject was based on the consideration of the headmaster that due to limited time and energy it was better to take the four informats. Data collection was done by interviewing techniques. atlas. ti and drawing conclusions were used to process the interview data. The result showed that the teachers at SDN Perak Barat VI had carried out their duties professionally. It is recommended for teacher profesionalism in the teaching and learning process.